A Course On English For Professional Communication For Engineering Undergraduates In A Technical University In Malaysia: A Needs Survey - M.SUBRAMANIAM , INDRA DEVI; MOHD RAUS , TEH ZANARIAH (2011)
In today 's climate of engineering education, there is an ever-increasing need to enhance the teaching and learning of professional communication skills which are often demanded by industrial advisory committees. In response to the above, this study aims to investigate the engineering undergraduates' English for Professional Communication needs as well as their perception on the importance of Professional communication skills. The subjects of the study comprise 326 engineering undergraduates. The instrument for data collection include a questionnaire. The quantitative data are analyzed using the Statistical Package for Social Sciences (SPSS) Program. The theoretical aspects of the needs analysis are based on the needs analysis model by Dudley-Evans and St. John (1998). The findings of the study show that the undergraduates' professional communication needs in terms of priority include grammar skills, responding and participating in interviews, conducting and participating in meetings, writing resume and cover letters for job applications, writing reports, delivering presentations, participating in group discussions and reading skills. These findings could be utilized for the designing of a syllabus and a textbook for a course on English for Professional Communication